The Myth of the Medieval Jewish Moneylender Volume II - Mell, Julie L. (Palgrave Studies in Cultural and Intellectual History, 2018)
This book challenges a common historical narrative, which portrays medieval Jews as moneylenders who filled an essential economic role in Europe. Where Volume I traced the development of the narrative in the nineteenth and twentieth centuries and refuted it with an in-depth study of English Jewry, Volume II explores the significance of dissolving the Jewish narrative for European history. It extends the study from England to northern France, the Mediterranean, and central Europe and deploys the methodologies of legal, cultural, and religious history alongside economic history. Each chapter offers a novel interpretation of key topics, such as the Christian usury campaign, the commercial revolution, and gift economy / profit economy, to demonstrate how the revision of Jewish history leads to new insights in European history. .